2013
DOI: 10.1002/ijc.28016
|View full text |Cite
|
Sign up to set email alerts
|

Dietary antioxidants and risk of Barrett's esophagus and adenocarcinoma of the esophagus in an Australian population

Abstract: While dietary antioxidants are emerging as potentially modifiable risk factors for esophageal adenocarcinoma (EAC), studies on dietary antioxidants and its precursor Barrett's esophagus (BE) are limited. The present study extends previous work on BE by investigating risks of nondysplastic BE, dysplastic BE and EAC associated with intake of antioxidants such as vitamin C, vitamin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 44 publications
0
42
0
Order By: Relevance
“…In vitro studies have demonstrated that treatment with antioxidants such as vitamin C and C-PTIO (2-[4-Carboxylphenyl]-4,4,5,5,-tetramethylimidazoline-1-oxyl-3-oxide) can prevent DNA damage by bile acid in OE33 cells and indeed are potentially more effective used in combination with acid-suppression therapy [137]. Further epidemiological studies have demonstrated a potential link between the intake of b-carotene and decreased risk of dysplastic BE [138]. While it remains an interesting potential treatment strategy, further studies are required to investigate the potential of antioxidant therapy.…”
Section: Antioxidant Therapymentioning
confidence: 96%
“…In vitro studies have demonstrated that treatment with antioxidants such as vitamin C and C-PTIO (2-[4-Carboxylphenyl]-4,4,5,5,-tetramethylimidazoline-1-oxyl-3-oxide) can prevent DNA damage by bile acid in OE33 cells and indeed are potentially more effective used in combination with acid-suppression therapy [137]. Further epidemiological studies have demonstrated a potential link between the intake of b-carotene and decreased risk of dysplastic BE [138]. While it remains an interesting potential treatment strategy, further studies are required to investigate the potential of antioxidant therapy.…”
Section: Antioxidant Therapymentioning
confidence: 96%
“…As a result, 15 articles reporting 20 studies including 3955 esophageal cancer cases and 7063 controls were selected for the meta-analysis. 13,[24][25][26][27][28][29][30][31][32][33][34][35][36][37] The detailed processes of our literature search are shown in Figure 1. The main characters of these studies are presented in Table 1.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…An inverse correlation between physical activity and cancer has been demonstrated in many recently published studies as well: Apart from the association between physical activity and an overall healthy lifestyle (especially in relation to reduced body weight and fatness), physical activity might reduce cancer risk also through the induction of epigenetic modifications [44][45][46][47][48][49][50]. The inverse correlation between fruit/vegetable consumption and cancer risk is well established: these foods harbor many protective factors such as polyphenols, flavonoids and fibers which are known to blunt cancer development [33,[51][52][53][54][55][56][57][58][59]. This study was carried out entirely in an Italian, Caucasian population; hence, it was not possible to take race into account as a potential confounding factor.…”
Section: Discussionmentioning
confidence: 93%